2018
DOI: 10.21272/mmi.2018.2-15
|View full text |Cite
|
Sign up to set email alerts
|

Analytical view of online marketing tools in the dimension of marketing campaigns’ personalization in Slovakia

Abstract: The objective of the article is to enrich knowledge about marketing personalization of the optimization of marketing campaigns. In the article, differences in how customers perceive individual tools of marketing communication in the online environment were evaluated. When creating campaigns, only the customer's view of the product (segmentation) is often taken into account. This article recommends some bases depending on campaign optimization variables. From a methodological point of view, a homogeneity analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…The ttest and one-way ANOVA findings show no differences among attitudes to post-industrial tourism on the age, gender, and education factors. Such conclusions were similar as those in [36,[50][51][52] and opposite to the conclusions in [36][37][38]. At the same time, despite the statistically significant relations among indicators analysed, the respondents over 30 years old emphasised the hidden impact of the post-industrial tourism development on the environment.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The ttest and one-way ANOVA findings show no differences among attitudes to post-industrial tourism on the age, gender, and education factors. Such conclusions were similar as those in [36,[50][51][52] and opposite to the conclusions in [36][37][38]. At the same time, despite the statistically significant relations among indicators analysed, the respondents over 30 years old emphasised the hidden impact of the post-industrial tourism development on the environment.…”
Section: Discussioncontrasting
confidence: 51%
“…Using multiple linear regression, this study confirmed the statistically significant impact of variable tendencies on tourism development and the low impact of "word of mouth" on tourism development. Studies [47][48][49][50][51][52] have proven that integrating different digital instruments (social media marketing, search engine optimisation, mobile applications, etc.) increased the popularity of post-industrial tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers [50][51][52][53][54][55] justified why economic and marketing determinants of the competitive advantages formation have a significant value for creating a new potential and growing market share for the companies. At the same time, many scientific articles describe linkages between environment and economic indicators .…”
Section: Introductionmentioning
confidence: 99%
“…In English, «agile» means «lively, mobile,» but is more commonly translated as «flexible» [13]. In February 2001, 17 specialists developed «the Manifest of flexible methology of program software» -Agile Manifesto.…”
mentioning
confidence: 99%